A Rarely Observed Cause of Acute Appendicitis, Sessile Serrated Lesion: A Case Report and Review - Barut, Saime Gül; Şensu, Sibel; Kutlu, Sevcan; Gürbüz, Saliha Yeşim (Cerrahpaşa Medical Journal, 2020)
Epithelial neoplasms can be seen in 0.2-0.3% of appendectomies performed due to acute appendicitis and a few of them might have a serrated appearence. The sessile serrated lesion and traditional serrated adenoma, which are types of serrated polyps, are significant because of their precancerous nature. A 57 year old female patient was admitted hospital with an acute abdominal symptoms, due to acute appendicitis with abscess and perforation. After appendectomy, a mass located close to the apex was found, histopathological diagnosis of which was sessile serrated lesion. Macroscopic detection of sessile serrated lesions of appendix is difficult and they can be missed. However, these tumors should definitely not be missed because of their precancerous potential, coexistence with malignancy and dysplasia, aggressive progression rate and accompanying polyposis syndromes. After an appendectomy due to acute appendicitis, detailed, if needed, whole-organ sampling, and a periodic endoscopic examination is crucial. Cite this article as: Barut SG, Şensu S, Kutlu S, Gürbüz SY. A Rarely Observed Cause of Acute Appendicitis, Sessile Serrated Lesion: A Case Report and Review. Cerrahpaşa Med J 2020; 44(3): 157-160.